2014
DOI: 10.1071/wf13016
|View full text |Cite
|
Sign up to set email alerts
|

Is fire severity increasing in the Sierra Nevada, California, USA?

Abstract: Abstract. Research in the Sierra Nevada range of California, USA, has provided conflicting results about current trends of high-severity fire. Previous studies have used only a portion of available fire severity data, or considered only a portion of the Sierra Nevada. Our goal was to investigate whether a trend in fire severity is occurring in Sierra Nevada conifer forests currently, using satellite imagery. We analysed all available fire severity data, 1984-2010, over the whole ecoregion and found no trend in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 52 publications
0
42
2
Order By: Relevance
“…Examining trends from 1984 to 2006 for large ecoregions in the north-and southwest USA, Dillon et al [71] found no significant increase in the proportion of annual area burned at high severity for five of the six regions considered, with the southern Rockies being the exception. For the Sierra Nevada region (California), which was not covered in the previous study [71], Hanson & Odion [72,73] found no general increase in fire severity within the period 1984-2010. Considering ten national forests in California for the same period, Miller & Safford [74] found a significant increase in burn severity for yellow pine -mixed conifer forests.…”
Section: Have Fire Impacts Increased In Many Regionsmentioning
confidence: 93%
“…Examining trends from 1984 to 2006 for large ecoregions in the north-and southwest USA, Dillon et al [71] found no significant increase in the proportion of annual area burned at high severity for five of the six regions considered, with the southern Rockies being the exception. For the Sierra Nevada region (California), which was not covered in the previous study [71], Hanson & Odion [72,73] found no general increase in fire severity within the period 1984-2010. Considering ten national forests in California for the same period, Miller & Safford [74] found a significant increase in burn severity for yellow pine -mixed conifer forests.…”
Section: Have Fire Impacts Increased In Many Regionsmentioning
confidence: 93%
“…The area affected by high-severity fire, in which most of the canopy vegetation is killed, is also increasing [35,36] and contrasts starkly with fire regimes prior to European-American settlement [37] (but see [38]). With the increasing prominence of larger, higher severity fires on the landscape, it is important to understand how shifting fire regimes affect the floral and faunal diversity of these fire-prone systems.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of actual patterns in fire occurrence under changing climate, there is no ongoing trend in the proportion of fire that is high in severity in the dry Cascades of Oregon [40,41]; nor is there a trend in the amounts of high-severity fire in the southern Cascades of California [42], but data are only available since 1984. The upward trend in fire severity in the Sierra Nevada reported by Miller et al [43] and Miller and Safford [44] using an incomplete regional data set does not exist when all the currently available burn severity data are analyzed, using the more comprehensive U.S. government fire severity data base from Monitoring Trends in Burn Severity, or "MTBS", and using forest mapping that pre-dates the time series to avoid missing montane conifer forest that experiences higher severity fire and is later remapped as chaparral [45]. While increased fire in the future could help prevent further habitat decline, under current management habitat may still be limited and ultimately insufficient in the future for black- …”
Section: Fig (5)mentioning
confidence: 99%